2013
DOI: 10.1007/8904_2013_228
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Exonic Splicing Mutation in the TAZ (G4.5) Gene in a Case with Atypical Barth Syndrome

Abstract: The identification of a TAZ gene mutation, mRNA analysis, and monolysocardiolipin/cardiolipin ratio determination were important for the diagnosis and genetic counseling in this family with atypical Barth syndrome that was not found to be associated with 3-methylglutaconic aciduria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…4 , Table 1 ). Functional RNA analysis proved that this mutation causes retention of intron 6 and partial deletion of exon 7, confirming pathogenicity (r.[541 + 1_542-1 ins; r.553_583del]; p.Lys182Glnfs*4) (Fan et al 2013 ). The mutation has not been modelled in yeast.…”
Section: Discussionmentioning
confidence: 78%
“…4 , Table 1 ). Functional RNA analysis proved that this mutation causes retention of intron 6 and partial deletion of exon 7, confirming pathogenicity (r.[541 + 1_542-1 ins; r.553_583del]; p.Lys182Glnfs*4) (Fan et al 2013 ). The mutation has not been modelled in yeast.…”
Section: Discussionmentioning
confidence: 78%
“…Chen et al reported nine patients with familial EFE in four families inherited in X-linked recessive, autosomal dominant and autosomal recessive fashion [149]. Recent reports have associated mutations in the tafazzin (TAZ/G4.5) gene located on Xq28 with familial X-linked EFE and Barth syndrome, reported to result in structural changes in the foetal heart as early as 18 weeks of gestation [150,151]. In a summary, current evidence suggests that primary EFE is hereditary, occurs with no other demonstrable cause of unexplained HF while secondary EFE is associated with aortic stenosis or atresia and includes coarctation of the aorta, ventricular septal defect, anomalous origin of left coronary artery from the pulmonary artery, myocardial injury from any cause, and metabolic or carnitine deficiency.…”
Section: Aetiopathogenesismentioning
confidence: 99%
“…Endocardial thickening may be the consequence of persistent and increased wall tension in the ventricles possible secondary to injured myocardium, mitral regurgitation or both [140][141][142][143][144]. EFE is sporadic but familial cases have been reported [150,151]. The suggestions that EFE might have a viral aetiology stems from the observation of the similarity of its clinical presentation to that of chronic MC.…”
Section: Aetiopathogenesismentioning
confidence: 99%